2016
DOI: 10.1007/s11302-016-9524-5
|View full text |Cite
|
Sign up to set email alerts
|

UDP-glucose promotes neutrophil recruitment in the lung

Abstract: In addition to their role in glycosylation reactions, UDP-sugars are released from cells and activate widely distributed cell surface P2Y 14 receptors (P2Y 14 R). However, the physiological/pathophysiological consequences of UDPsugar release are incompletely defined. Here, we report that UDP-glucose levels are abnormally elevated in lung secretions from patients with cystic fibrosis (CF) as well as in a mouse model of CF-like disease, the βENaC transgenic (Tg) mouse. Instillation of UDP-glucose into wild-type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(78 citation statements)
references
References 55 publications
1
71
0
Order By: Relevance
“…inconsistence. It is known that UDPG could be released from Golgi to the extracellular space through a secretory pathway 30,31 , where UDPG bound to the receptor P2Y 14 for signal transduction [18][19][20]31,32 . Notably, the expression of P2Y 14 receptor was upregulated in IFN-γ/LPS-treated macrophages (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…inconsistence. It is known that UDPG could be released from Golgi to the extracellular space through a secretory pathway 30,31 , where UDPG bound to the receptor P2Y 14 for signal transduction [18][19][20]31,32 . Notably, the expression of P2Y 14 receptor was upregulated in IFN-γ/LPS-treated macrophages (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These findings imply that glycogen may exert important biological effects through metabolic pathways beyond its role as a reservoir of glucose. In support of this notion, UDPglucose (UDPG), a glycogen metabolic intermediate, has been shown to act as a ligand for purigenic receptor P2Y 14 , thus directly triggering signal transduction [18][19][20] .…”
mentioning
confidence: 98%
“…P2Y 14 receptors activation promotes chemotaxis in human neutrophils, as studied in cystic fibrosis (Sesma et al, 2016), the release of proinflammatory cytokines from renal intercalated cells in sterile inflammation (Azroyan et al, 2015), and the degranulation of mast cells (Gao, Wei, Jayasekara, & Jacobson, 2013). Thus, P2Y 14 receptor antagonists are being developed for anti‐inflammatory applications (Junker et al, 2016).…”
Section: P2y Receptors In Immune and Pulmonary Functionmentioning
confidence: 99%
“…This receptor subtype is expressed by leukocytes, thus pointing out a possible effect in inflammation [246]. It has been shown that the activation of P2Y 14 Rs promoted the chemotaxis of neutrophils [247,248], specifically in the lungs [249]. and maturation [133].…”
Section: P2y 14mentioning
confidence: 99%